2020
DOI: 10.1097/pas.0000000000001468
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantitation of CD8-positive T Cells Predicts Prognosis in Colonic Adenocarcinoma With Mucinous, Signet Ring Cell, or Medullary Differentiation Independent of Mismatch Repair Protein Status

Abstract: Despite their association with DNA mismatch repair (MMR) protein deficiency, colonic adenocarcinomas with mucinous, signet ring cell, or medullary differentiation have not been associated with improved survival compared with conventional adenocarcinomas in most studies. Recent studies indicate that increased T-cell infiltration in the tumor microenvironment has a favorable prognostic effect in colonic adenocarcinoma. However, the prognostic effect of tumor-associated T cells has not been evaluated in histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Several studies have been reported that CD8 + cell infiltration is associated with better prognosis 11 , 12 . In other reports, CD8 + cell was also associated with recurrence, progression, or lymph node invasion 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been reported that CD8 + cell infiltration is associated with better prognosis 11 , 12 . In other reports, CD8 + cell was also associated with recurrence, progression, or lymph node invasion 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al evaluated 520 colorectal carcinomas with mucinous differentiation and demonstrated that high TILs (defined as ≥ 2 TILs per five high-power fields by manual quantitation) was a predictor of disease-free survival, independent of MMR status, BRAF mutation status and histological grade. 87 Similarly, Hartman et al demonstrated that CD8 + T cell density using quantitative digital image analysis of the tumour centre and invasive margin was an independent predictor of disease-free survival in colonic adenocarcinomas with mucinous differentiation 41 (Figure 4). The data indicate that TILs within adenocarcinomas with mucinous differentiation may be an important prognostic feature.…”
Section: O L O R E C T a L C A N C E R W I T H M U C I N O U S D I F ...mentioning
confidence: 91%
“…Similarly, Hartman et al . demonstrated that CD8 + T cell density using quantitative digital image analysis of the tumour centre and invasive margin was an independent predictor of disease‐free survival in colonic adenocarcinomas with mucinous differentiation 41 (Figure 4). The data indicate that TILs within adenocarcinomas with mucinous differentiation may be an important prognostic feature.…”
Section: Immune Response As a Prognostic And Predictive Biomarker In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The AUROC for CD8 + T-cell density in the tumor center for the stage II to III cohort was 0.66 (0.59 to 0.73, 95% CI), with an optimal cutoff of 109/mm 2 . Using these cutoffs, the tumors were separated into 3 categories (low, intermediate, and high), as previously described 30. For the survival analyses, the intermediate and high CD8 + T-cell density categories were combined into 1 category (intermediate/high CD8 + T-cell density) given the results of our prior study and those using the immunoscore that demonstrated similar survival for these 2 categories 14,30,31…”
Section: Methodsmentioning
confidence: 99%